A nickel-cobalt-manganese-aluminum quaternary precursor material, a preparation method thereof, and an electrode and a battery
Patent Information
- Application Number
- CN202611196011.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]但受金属离子沉淀化学性质差异限制,现有一步共沉淀制备NCMA前驱体技术仍存在诸多难以克服的技术难题
[0007]有鉴于此,本发明的目的是提供一种镍钴锰铝四元前驱体材料及其制备方法和电极、电池,实现了铝元素均匀分散,同时兼顾前驱体高球形度、高振实密度。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and in particular to a nickel-cobalt-manganese-aluminum quaternary precursor material, its preparation method, and electrodes and batteries. Background Technology
[0002] With the rapid development of new energy vehicles and energy storage, the market is placing higher demands on the energy density, cycle stability, and safety performance of lithium-ion battery cathode materials. High-nickel ternary nickel-cobalt-manganese (NCM) layered oxide cathode materials have been widely used in power lithium-ion battery systems due to their high reversible capacity. However, traditional high-nickel NCM materials have significant drawbacks: they are prone to irreversible H2-H3 phase transitions during charging and discharging, leading to continuous accumulation of lattice stress and microcracks in the particles, resulting in continuous side reactions in the electrolyte and degradation of active materials; simultaneously, the high-nickel system has poor thermal stability, posing safety hazards.
[0003] Nickel-cobalt-aluminum (NCA) cathode materials exhibit superior cycle and thermal stability compared to conventional NCMs due to the lattice stabilizing effect of aluminum. However, the absence of manganese in this material makes particle morphology control during preparation difficult, leads to gas expansion during storage, and results in higher production costs. To combine the advantages of both NCM and NCA materials, the industry has proposed introducing aluminum into the nickel-cobalt-manganese system to construct nickel-cobalt-manganese-aluminum (NCMA) quaternary layered cathode materials. The corresponding quaternary precursor generally has the formula Ni. x Co y Mn z Al w (OH)₂ (x+y+z+w=1) is mixed with lithium salt and then subjected to high-temperature lithiation and sintering to obtain LiNi. x Co y Mn z Al w O2 quaternary cathode. In this system, the nickel component mainly provides high reversible capacity; the cobalt component can suppress lithium-nickel cation mixing and maintain the layered crystal structure; the manganese component improves the thermal stability of the material and reduces raw material costs; aluminum strengthens the lattice framework through stronger Al-O bonds, effectively suppressing irreversible phase transitions during charge and discharge, alleviating the initiation of microcracks in particles, reducing oxygen release from the lattice, and simultaneously improving the cycle life and thermal safety of the cathode material. It is also expected to achieve low cobalt content, alleviating the cost pressure caused by fluctuations in cobalt resource prices.
[0004] Currently, the preparation of NCMA precursors mainly follows two routes: one is a one-step co-precipitation process, in which nickel, cobalt, manganese, and aluminum salts are prepared into a mixed metal salt solution, and then co-precipitated with a precipitant and a complexing agent in a reactor to directly synthesize the quaternary precursor; the other is a two-step composite process, in which a nickel-cobalt-manganese ternary precursor is first prepared, and then aluminum doping is achieved by adding an external aluminum source in a solid-state manner during the subsequent lithiation sintering stage. Compared with the solid-state aluminum doping route, the one-step co-precipitation process is theoretically easier to achieve a uniform distribution of aluminum within the particles, and has become a key research direction.
[0005] However, due to the differences in the chemical properties of metal ion precipitation, the existing one-step co-precipitation technology for preparing NCMA precursors still faces many insurmountable technical challenges. Aluminum ions hardly form stable complexes with ammonia, and the solubility product of aluminum hydroxide is much lower than that of nickel, cobalt, and manganese hydroxides. In conventional co-precipitation systems, aluminum ions are prone to rapid supersaturation in localized areas and preferentially precipitate amorphous flocculent aluminum hydroxide, making it difficult to uniformly embed into the nickel-cobalt-manganese hydroxide matrix. This ultimately leads to radial segregation of aluminum, resulting in aluminum-poor particle cores and aluminum-rich particle surfaces. Uneven aluminum distribution further triggers a series of derivative problems: aluminum-rich areas are prone to generating inert LiAlO2 impurities during sintering, reducing the material's reversible capacity; aluminum-deficient areas cannot play a lattice stabilizing role, and microcracks are easily generated during the cycling process of the finished cathode. At the same time, the free precipitated flocculent aluminum hydroxide interferes with the normal growth of spherical secondary particles, destroying particle sphericity and easily forming a loose, porous, cauliflower-like morphology, causing a decrease in the tap density and an increase in the specific surface area of the precursor. On the one hand, this increases the difficulty of compacting the positive electrode sheet; on the other hand, it increases the risk of electrolyte side reactions and battery gas generation. Furthermore, aluminum hydroxide is an amphoteric hydroxide, resulting in an extremely narrow pH process window for the NCMA co-precipitation system, meaning even small parameter fluctuations can alter aluminum precipitation behavior. Multiple parameters, such as temperature, ammonia concentration, feed rate, and stirring intensity, are highly coupled, making batch consistency control under mass production conditions far more difficult than with conventional ternary precursors. In addition, the porous morphology easily traps impurities such as sulfate and sodium ions; the washing stage also carries the risk of surface aluminum dissolution, creating a dilemma where impurity removal and elemental composition stability are difficult to achieve simultaneously.
[0006] Therefore, how to achieve uniform dispersion of aluminum in a co-precipitation system, while taking into account the high sphericity and high tap density of the precursor, and to stably achieve large-scale consistent production, is a key technical bottleneck that urgently needs to be solved for the industrialization of high-quality nickel-cobalt-manganese-aluminum quaternary precursors. Summary of the Invention
[0007] In view of this, the purpose of this invention is to provide a nickel-cobalt-manganese-aluminum quaternary precursor material, its preparation method, electrodes, and batteries, which achieve uniform dispersion of aluminum elements while taking into account the high sphericity and high tap density of the precursor.
[0008] The present invention solves the above-mentioned technical problems through the following technical means:
[0009] In a first aspect, embodiments of the present invention provide a method for preparing a nickel-cobalt-manganese-aluminum quaternary precursor material, wherein the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni x Co y Mn z Al w (OH)₂, satisfying x + y + z + w = 1, and 0.80 ≤ x ≤ 0.90, 0.04 ≤ y ≤ 0.08, 0.04 ≤ z ≤ 0.08, 0.01 ≤ w ≤ 0.03; the preparation method includes the following steps:
[0010] Weigh aluminum sulfate octadechydrate and add it to deionized water to prepare an aluminum sulfate solution. Add an anionic polar modifier to the aluminum sulfate solution and stir at 120–180 rpm for 30–50 min to obtain [Al(OH)4]. - Homogeneous solution;
[0011] Weigh nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate monohydrate according to the target product molar ratio, dissolve them in deionized water, and prepare a homogeneous sulfate solution. Preheat the reactor to 50-60°C and maintain the temperature. Purge with nitrogen to maintain a pressure of 0.02-0.04 MPa. Use two pumps to pump the homogeneous sulfate solution and sodium hydroxide solution into the reactor respectively. Control the pH in the reactor to 10.5-11.0. Stir the reaction at 350-450 rpm for 9-13 hours to obtain a positively charged NCM framework suspension.
[0012] [Al(OH)4] was stirred at 50–60°C and 260–340 rpm. - The homogeneous solution was added dropwise at a constant rate to the positively charged NCM framework suspension. After the addition was completed, the mixture was stirred continuously at a constant temperature for 3 to 7 hours. Then, the pH was adjusted to 11.0 to 11.2, and the mixture was aged in a sealed container at 50 to 60°C for 3 to 5 hours to obtain the precursor slurry.
[0013] The precursor slurry was centrifuged to separate the precipitate, which was then washed with a weakly alkaline solution with a pH of 8.5–9.5. The washed precipitate was then subjected to vacuum gradient drying to obtain the nickel-cobalt-manganese-aluminum quaternary precursor material.
[0014] By adopting the above technical solution, on the one hand, it addresses the issue of AI 3+The inherent defects of aluminum ions, such as extremely low solubility, precipitation kinetics much faster than nickel-cobalt-manganese ions, and a tendency for spontaneous disordered nucleation and aggregation, are addressed by using an anionic polar regulator to directionally alter the thermodynamic and kinetic pathways of aluminum ion hydrolysis. This suppresses the instantaneous precipitation of free aluminum ions, completely transforming them into strongly negatively charged tetrahydroxyaluminum coordination intermediates with no spontaneous nucleation ability. Without complexing transition metal ions, this imparts directional electrostatic adsorption properties to the aluminum source, solving the problem of random segregation of the aluminum phase. Furthermore, ammonia and organic complexing agents are completely eliminated throughout the process. A slow crystallization mechanism with low supersaturation avoids the problems of disordered grains, excessive porosity, and disordered defects in traditional complexing systems. The orderly growth of nickel-cobalt-manganese hydroxide is induced in an inert, closed environment, constructing a rigid spherical framework with uniform surface potential and regularly distributed defect sites. This provides a unique attachment site for the subsequent site-specific and uniform adsorption of aluminum intermediates, preventing selective enrichment of aluminum elements from the structural source. Finally, relying on the positively charged NCM framework and [Al(OH)4]... - The interface effect of spontaneous adsorption of positive and negative charges allows negatively charged aluminum intermediates to uniformly fill framework defects solely through electrostatic driving force, rather than through random precipitation growth. This avoids the problem of aluminum-rich surfaces and aluminum-poor cores caused by aluminum kinetic mismatch in traditional processes, achieving a uniform micro-atomic distribution of aluminum. Furthermore, the use of a weakly alkaline microenvironment (pH 11.00–11.20) induces in-situ solidification of the adsorbed aluminum intermediates, enabling trivalent aluminum atoms to precisely fill lattice vacancies and grain boundary defects in the NCM framework, forming a stable homogeneous solid solution structure and preventing the formation of inert LiAlO2 impurities. Simultaneously, the micro-volume compensation effect of the aluminum atom solidification process fills in-situ micropores and intergranular gaps within the particles, achieving self-sealing and dense reconstruction, overcoming the porous defects of the precursor.
[0015] Preferably, the concentration of the aluminum sulfate solution is 0.17–0.23 mol / L to ensure the monodisperse stability of the aluminum intermediate and obtain a homogeneous solution in which aluminum sulfate is completely dissolved. 0.05–0.15 g of anionic polar modifier is added per liter of the aluminum sulfate solution. The anionic polar modifier is used to directionally regulate the aluminum ion hydrolysis pathway, construct the negatively charged aluminum hydroxyl intermediate, and inhibit the spontaneous flocculent precipitation of Al(OH)3. The anionic polar modifier only alters the thermodynamics and interfacial charge characteristics of aluminum ion hydrolysis and does not react with Ni. 2+ Co 2+ Mn 2+ Al 3+ A complexation reaction occurs.
[0016] Preferably, the anionic polarity modifier is selected from at least one of sodium dodecylbenzenesulfonate, sodium dodecyl sulfonate, sodium tetradecyl sulfonate, sodium tartrate, sodium citrate, sodium gluconate, and sodium lignin sulfonate.
[0017] Preferably, the total metal ion concentration in the homogeneous sulfate solution is 1.7–2.1 mol / L to achieve low-supersaturation steady-state growth of NCM and obtain a dense spherical NCM framework. And / or, the concentration of the sodium hydroxide solution is 17–21 wt%, which is beneficial for the stacking of growth grains to form a dense spherical precursor framework.
[0018] Preferably, the homogeneous sulfate solution is pumped into the reactor at a rate of 18–28 mL / min; and / or, the sodium hydroxide solution is titrated using a PID closed-loop follow-up titration method. By dynamically adjusting the precipitant feed rate in real time using PID closed-loop follow-up titration, the pH of the reaction system is kept constant, eliminating pH fluctuations and localized over-alkaliness issues caused by intermittent and constant-rate titrations, thus ensuring the uniformity of NCM framework particle growth and surface potential.
[0019] Preferably, the [Al(OH)4] - The homogeneous solution was added dropwise to the positively charged NCM framework suspension at a constant rate of 7–13 mL / min. This ensured that the aluminum intermediates were uniformly dispersed in the liquid phase with stirring, allowing sufficient time for them to be uniformly adsorbed on the surface of the NCM framework and at grain boundary defects, thus avoiding localized agglomeration of aluminum and ensuring a uniform distribution of aluminum throughout the entire structure.
[0020] Preferably, the vacuum degree of the vacuum gradient drying is -0.11 to 0.07 MPa, and the vacuum gradient drying procedure is as follows: first drying at 35 to 45°C for 1 to 3 hours, then drying at 55 to 65°C for 2 to 4 hours, and finally drying at 75 to 85°C for 2 to 4 hours. This avoids the rapid structural collapse of the precursor due to rapid heating, fully preserving the high sphericity and high density microstructure; at the same time, it prevents secondary segregation caused by thermal migration of aluminum components, ensuring uniform elemental distribution in the final product.
[0021] Secondly, embodiments of the present invention also provide a nickel-cobalt-manganese-aluminum quaternary precursor material, prepared using the preparation method described in the first aspect. The nickel-cobalt-manganese-aluminum quaternary precursor material has no structural defects and uniform elemental solid solution, which can be stably inherited into the sintered cathode material. It effectively suppresses the irreversible H2-H3 phase transition and microcrack initiation during charge and discharge processes, reduces the risk of battery gas expansion and capacity decay, and significantly improves the cycle life, rate performance, and thermal safety of the high-nickel cathode.
[0022] Thirdly, embodiments of the present invention also provide an electrode comprising the nickel-cobalt-manganese-aluminum quaternary precursor material as described in the second aspect.
[0023] Fourthly, embodiments of the present invention also provide a battery, characterized in that the battery includes electrodes as described in the third aspect. Detailed Implementation
[0024] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0025] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0026] In conventional preparation methods of nickel-cobalt-manganese-aluminum quaternary precursor materials, Al 3+ Precipitation kinetics are much faster than those of Ni, Co, and Mn. During the reaction, aluminum preferentially nucleates or lags behind in doping, making dynamic rate matching impossible. This inevitably leads to segregation and a porous structure in the final product. The method for preparing the nickel-cobalt-manganese-aluminum quaternary precursor material in this application utilizes the surface charge differences of different metal hydroxides to construct a dynamic heterogeneous electrostatic adsorption interface, achieving a three-step heterogeneous assembly mechanism: first, lattice framework shaping; then, atomic-level aluminum intercalation and locking; and finally, overall sealing of pores. This preparation method achieves uniform distribution of aluminum within the precursor grains, grain boundaries, and surface, with no aluminum-rich / aluminum-poor regions. After sintering, there is no inert LiAlO2 impurity phase, and the resulting precursor exhibits no loose cauliflower morphology and a significantly higher tap density than traditional co-precipitated products.
[0027] Specifically, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni x Co y Mn z Al w (OH)₂ satisfies x + y + z + w = 1, and 0.80 ≤ x ≤ 0.90, 0.04 ≤ y ≤ 0.08, 0.04 ≤ z ≤ 0.08, 0.01 ≤ w ≤ 0.03. Its preparation method includes the following steps:
[0028] (1) According to the aluminum doping ratio w of the target product, weigh aluminum sulfate octahydrate and add it to deionized water to prepare an aluminum sulfate solution with a concentration of 0.17-0.23 mol / L; add 0.05-0.15 g of anionic polar regulator to each liter of aluminum sulfate solution, stir at room temperature and 120-180 rpm for 30-50 min to directionally regulate the aluminum ion hydrolysis pathway and completely suppress free Al 3+ Disordered nucleation and flocculent Al(OH)3 precipitate were used to prepare a monodisperse, highly stable tetrahydroxyaluminate anionic intermediate [Al(OH)4] with a Zeta potential of -30 to -20 mV. - Homogeneous solution, sealed and allowed to stand for later use.
[0029] In this step, the anionic polarity modifier is selected from at least one of sodium dodecylbenzenesulfonate, sodium dodecyl sulfonate, sodium tetradecyl sulfonate, sodium tartrate, sodium citrate, sodium gluconate, and sodium lignin sulfonate.
[0030] (2) Weigh nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate monohydrate according to the target product molar ratio, dissolve them in deionized water, and prepare a homogeneous sulfate solution with a total metal ion concentration of 1.7–2.1 mol / L; prepare a sodium hydroxide solution with a mass fraction of 17–21% as the sole precipitant. Preheat the closed continuous reactor to 50–60°C, and purge with nitrogen to maintain a slightly positive pressure inert atmosphere of 0.02–0.04 MPa. Do not add ammonia or any metal complexing agents throughout the process. Use a dual-pump synchronous feeding method. One pump is used to pump in the homogeneous sulfate solution at a feed rate of 18–28 mL / min; the other pump is used to pump in the 17–21% sodium hydroxide solution. The sodium hydroxide solution is titrated by a PID closed-loop follow-up titration, and the steady-state pH in the reactor is controlled at 10.5–11.0. Stir the reaction at 350–450 rpm for 9–13 hours. After the reaction, the mixture is sieved through a 180-220 mesh to remove ultrafine powder and large particle impurities, resulting in a positively charged NCM framework suspension with a median particle size of 3.2-3.8 μm, a surface Zeta potential of +15-+25 mV, dense grain packing, and uniformly distributed defects. The suspension is then kept at a constant temperature and sealed for later use.
[0031] In this step, the PID closed-loop follow-up titration is specifically as follows: First, the equipment collects the instantaneous pH value in the vessel in real time. Then, the sodium hydroxide feed flow rate is dynamically and in real time adjusted through the PID algorithm. Then, when the pH is too low, the addition of alkali is automatically accelerated, and when the pH is too high, the addition of alkali is automatically slowed down, so that the pH in the vessel is always controlled within the range of 10.5 to 11.0.
[0032] (3) Maintain the reactor temperature at 50-60℃ and the stirring speed at 260-340 rpm, and add [Al(OH)4] -The homogeneous solution was added dropwise to the positively charged NCM framework suspension at a constant rate of 7–13 mL / min, and the total amount of aluminum source was precisely controlled so that the metal elements in the system met the ratio of x+y+z+w=1. The adsorption reaction was carried out under constant temperature and continuous stirring for 3–7 h. Relying on the heteroelectrostatic adsorption, the negatively charged aluminum intermediate was unidirectionally, uniformly and completely adsorbed on the surface of the spherical framework, grain boundaries and lattice defect sites, thus completing the uniform intercalation of aluminum elements throughout the entire domain. After the adsorption reaction was completed, the pH of the system was finely adjusted to 11.00–11.20 using 0.3–0.7 mol / L dilute sodium hydroxide solution, and the system was aged at a constant temperature of 50–60℃ for 3–5 hours in a sealed environment. This induced in-situ solid-phase solidification reaction of the adsorbed negatively charged aluminum intermediate, with aluminum atoms precisely filling the vacancies and grain boundary defects in the NCM framework lattice to form a quaternary homogeneous solid solution structure. At the same time, relying on the volume-filling effect of aluminum atom solidification, the micropores and interstitial defects inside the particles were repaired, achieving self-sealing and dense reconstruction, resulting in a spherical, regular, and dense precursor slurry.
[0033] (4) The precursor slurry was centrifuged to separate solid and liquid components. The precipitate was washed 3 to 5 times with a weakly alkaline solution at pH 8.5 to 9.5 and a temperature of 40 to 50°C. Each wash was soaked for 10 to 20 minutes and rinsed with low-speed stirring at 120 to 180 rpm to remove sodium ions and sulfate impurities while avoiding the dissolution of aluminum components. The washed precipitate was then subjected to gradient drying under a vacuum of -0.11 to -0.07 MPa. Specifically, it was pre-dried at 35 to 45°C for 1 to 3 hours, dried at a constant temperature of 55 to 65°C for 2 to 4 hours, and then deep-dried at 75 to 85°C for 2 to 4 hours to finally obtain a highly homogeneous, highly dense, and segregated nickel-cobalt-manganese-aluminum quaternary precursor material.
[0034] In this step, the weak alkaline solution is controlled by adding a small amount of 1.2-2.8 wt% low-concentration sodium hydroxide solution to conventional deionized water. The pH is monitored online throughout the process to precisely adjust and stabilize the pH of the washing water to the range of 8.5-9.5, avoiding excessive strong alkali that may cause impurities to remain or too weak alkali that may cause aluminum to dissolve.
[0035] In practice, the order of steps (1) and (2) can be interchanged.
[0036] The nickel-cobalt-manganese-aluminum quaternary precursor material prepared by this invention can be used to prepare a nickel-cobalt-manganese-aluminum quaternary cathode material with high structural stability and long cycle life through precise lithium mixing and segmented high-temperature solid-state sintering. This achieves a homogeneous and dense precursor structure with low defects, solving the problems of uneven aluminum element distribution, numerous segregated impurities, severe microcracks, and rapid cycle decay in traditional NCMA cathodes.
[0037] Specifically, the cathode material of the present invention comprises a nickel-cobalt-manganese-aluminum quaternary precursor material and a lithium source, wherein the lithium source is battery-grade lithium carbonate or lithium hydroxide, and the molar ratio of lithium in the lithium source to the total metals of the precursor is 1.02 to 1.06:1. The preparation method of the cathode material of the present invention is as follows:
[0038] S1. Place the nickel-cobalt-manganese-aluminum quaternary precursor material and the lithium source into a high-speed powder mixer and mix at 300-500 rpm for 20-40 minutes to ensure that the lithium source and precursor particles are uniformly coated on the entire surface without local lithium deficiency / lithium rich areas, thus providing a basis for subsequent uniform lithiation and solid solution, and finally obtain a mixed powder.
[0039] S2. The mixed powder is transferred to an oxygen-atmosphere tube furnace for segmented sintering, with an oxygen concentration ≥95% throughout the process. The segmented sintering is as follows: ① Heating to 450℃ at a rate of 3-5℃ / min and holding for 2-3 hours to completely remove precursor structural water and trace residual impurities, completing the initial phase transition from hydroxide to oxide, and avoiding particle cracking and structural collapse caused by rapid heating; ② Heating to 750℃ at a rate of 2-4℃ / min and holding for 2-3 hours to complete the diffusion solid solution of lithium into the quaternary metal oxide lattice, initially constructing a complete layered cathode lattice structure; ③ Heating to 830℃ at a rate of 1-2℃ / min and holding for 10-14 hours to complete grain growth, lattice regularization, and defect repair, forming a highly crystallized, uniformly stressed, and structurally stable NCMA layered cathode material; ④ Naturally cooling to room temperature with the furnace to avoid lattice stress and micro-defects caused by rapid cooling.
[0040] S3. The sintered product from step S2 is subjected to 200-300 mesh sieve screening, iron removal, and powder homogenization treatment to obtain the final state NCMA cathode material, with the general formula LiNi. x Co y Mn z Al w O, satisfying x+y+z+w=1, and 0.80≤x≤0.90, 0.04≤y≤0.08, 0.04≤z≤0.08, 0.01≤w≤0.03.
[0041] Using the cathode material prepared above as the core active raw material, and combined with conventional conductive agents, binders and solvent systems, a special positive electrode for power batteries is prepared through homogenization, coating, rolling, slicing and vacuum drying processes. The specific preparation process of the electrode will not be described in this application.
[0042] In specific implementation, the following examples can be referred to:
[0043] Example 1
[0044] In this embodiment, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni. 0.86 Co 0.06 Mn0.06 Al 0.02 (OH)₂ is prepared as follows:
[0045] (1) Based on the aluminum doping ratio w=0.02, weigh 18.22g of aluminum sulfate octahydrate, add deionized water to make up to 200mL, and prepare a 0.17 mol / L aluminum sulfate solution (lower limit of concentration); add 0.01g of sodium citrate as a polarity modifier, and stir at room temperature and 120 rpm for 50 min to prepare a monodisperse [Al(OH)4] with a Zeta potential of -20 mV. - Homogeneous solution, sealed and allowed to stand for later use.
[0046] (2) Press Ni 0.86 Co 0.06 Mn 0.06 Molar proportions were determined by weighing 87.71 g of nickel sulfate hexahydrate, 7.27 g of cobalt sulfate heptahydrate, and 6.13 g of manganese sulfate monohydrate, and adding deionized water to a final volume of 200 mL to prepare a homogeneous sulfate solution with a total metal ion concentration of 1.7 mol / L. 17.00 g of sodium hydroxide was also weighed and added to a final volume of 100 mL of deionized water to prepare a 17% sodium hydroxide solution, which was used as a precipitant. The reactor was preheated to 50°C, and nitrogen gas was introduced to maintain a slightly positive pressure inert atmosphere of 0.02 MPa. Simultaneous dual-pump feeding was used, with the sulfate solution feed rate at 18 mL / min. The sodium hydroxide solution was titrated using a PID closed-loop system to precisely control the steady-state pH at 10.5. The reaction was carried out at 350 rpm for 9 hours. After the reaction, the mixture was sieved through a 180-mesh screen to remove impurities, resulting in a positively charged NCM framework suspension with a median particle size of 3.2 μm, a surface Zeta potential of +15 mV, and dense grains. The suspension was then kept at a constant temperature and sealed for later use.
[0047] (3) Maintain the temperature inside the reactor at 50℃ and the rotation speed at 260 rpm, [Al(OH)4] - The homogeneous solution was added dropwise to the positively charged NCM framework suspension at a constant rate of 7 mL / min, and the adsorption reaction was carried out by stirring at a constant temperature for 3 h. The pH of the system was finely adjusted to 11.00 using 0.3 mol / L dilute sodium hydroxide solution, and the mixture was aged in a sealed container at 50 °C for 3 h to obtain the precursor slurry.
[0048] (4) The precursor slurry was centrifuged to separate solids and liquids. The precipitate was washed three times with a weakly alkaline solution at 40℃ and pH=8.5, with each soaking lasting 10 min and followed by low-speed stirring at 120 rpm. Gradient drying was performed under a vacuum of -0.07 MPa: pre-drying at 35℃ for 1 h, constant-temperature drying at 55℃ for 2 h, and deep drying at 75℃ for 2 h to obtain Ni. 0.86 Co 0.06 Mn 0.06 Al 0.02(OH)2 precursor materials.
[0049] Example 2
[0050] In this embodiment, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni. 0.84 Co 0.06 Mn 0.07 Al 0.03 (OH)₂ is prepared as follows:
[0051] (1) Based on the aluminum doping ratio w=0.03, weigh 24.43g of aluminum sulfate octahydrate, add deionized water to make up to 200mL, and prepare a 0.23 mol / L aluminum sulfate solution (lower limit of concentration); add 0.03g of sodium gluconate as a polarity modifier, and stir at room temperature and 180 rpm for 30 min to prepare a monodisperse [Al(OH)4] with a Zeta potential of -30 mV. - Homogeneous solution, sealed and allowed to stand for later use.
[0052] (2) Press Ni 0.84 Co 0.06 Mn 0.07 Molar proportions were determined by weighing 106.78 g of nickel sulfate hexahydrate, 8.98 g of cobalt sulfate heptahydrate, and 9.07 g of manganese sulfate monohydrate, and adding deionized water to a final volume of 200 mL to prepare a homogeneous sulfate solution with a total metal ion concentration of 2.1 mol / L. 21.00 g of sodium hydroxide was also weighed and added to a final volume of 100 mL of deionized water to prepare a 21% sodium hydroxide solution, which was used as a precipitant. The reactor was preheated to 60°C, and nitrogen gas was introduced to maintain a slightly positive pressure inert atmosphere of 0.04 MPa. A dual-pump synchronous feed system was used, with the sulfate solution feed rate at 28 mL / min. The sodium hydroxide solution was titrated using a PID closed-loop system to precisely control the steady-state pH of the reactor at 11.0. The reaction was carried out at 450 rpm for 13 hours. After the reaction, the mixture was sieved through a 220-mesh screen to remove impurities, resulting in a positively charged NCM framework suspension with a median particle size of 3.8 μm, a surface Zeta potential of +25 mV, dense grains, and uniform defects. The suspension was then kept at a constant temperature and sealed for later use.
[0053] (3) Maintain the temperature inside the reactor at 60℃ and the rotation speed at 340 rpm, [Al(OH)4] - The homogeneous solution was added dropwise to the positively charged NCM framework suspension at a constant rate of 13 mL / min, and the adsorption reaction was carried out at a constant temperature with stirring for 7 h. The pH of the system was finely adjusted to 11.2 using 0.7 mol / L dilute sodium hydroxide solution, and the mixture was aged in a sealed container at 60 °C for 5 h to obtain the precursor slurry.
[0054] (4) The precursor slurry was centrifuged to separate solids and liquids. The precipitate was washed five times with a weakly alkaline solution at 50℃ and pH=9.5, with each soaking lasting 20 min and followed by low-speed stirring at 180 rpm. Gradient drying was performed under a vacuum of -0.11 MPa: pre-drying at 45℃ for 3 h, constant-temperature drying at 65℃ for 4 h, and deep drying at 85℃ for 4 h to obtain Ni. 0.84 Co 0.06 Mn 0.07 Al 0.03 (OH)2 precursor materials.
[0055] Example 3
[0056] In this embodiment, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni. 0.90 Co 0.04 Mn 0.04 Al 0.02 (OH)₂ is prepared as follows:
[0057] (1) Based on the aluminum doping ratio w=0.02, weigh 21.32g of aluminum sulfate octadechydrate, add deionized water to make up to 200mL, and prepare a 0.20 mol / L aluminum sulfate solution (lower limit of concentration); add 0.02g of sodium lignosulfonate as a polarity modifier, and stir at room temperature and 150 rpm for 40min to prepare a monodisperse [Al(OH)4] with a Zeta potential of -24mV. - Homogeneous solution, sealed and allowed to stand for later use.
[0058] (2) Press Ni 0.90 Co 0.04 Mn 0.04 Molar ratios were determined as follows: 101.52 g of nickel sulfate hexahydrate, 5.94 g of cobalt sulfate heptahydrate, and 5.17 g of manganese sulfate monohydrate were weighed and diluted to 200 mL with deionized water to prepare a homogeneous sulfate solution with a total metal ion concentration of 1.9 mol / L. 19.00 g of sodium hydroxide was weighed and diluted to 100 mL with deionized water to prepare a 19% sodium hydroxide solution as a precipitant. The reactor was preheated to 55°C, and nitrogen gas was introduced to maintain a slightly positive pressure inert atmosphere of 0.03 MPa. Simultaneous dual-pump feeding was used, with the sulfate solution feed rate at 22 mL / min. The sodium hydroxide solution was titrated using a PID closed-loop follower titration method to precisely control the steady-state pH of the reactor at 10.8. The reaction was stirred at 400 rpm for 10 h. After the reaction, impurities were removed by sieving through a 200-mesh sieve to obtain a positively charged NCM framework suspension with a median particle size of 3.6 μm, which was then kept at a constant temperature and sealed for later use.
[0059] (3) Maintain the temperature inside the reactor at 55℃ and the rotation speed at 290 rpm, [Al(OH)4] -The homogeneous solution was added dropwise to the positively charged NCM framework suspension at a constant rate of 9 mL / min, and the adsorption reaction was carried out at a constant temperature with stirring for 6 h. The pH of the system was finely adjusted to 11.15 using 0.4 mol / L dilute sodium hydroxide solution, and the mixture was aged at 55 °C in a sealed environment for 4.5 h to obtain the precursor slurry.
[0060] (4) The precursor slurry was centrifuged to separate solids and liquids. The precipitate was washed four times with a weakly alkaline solution at 45℃ and pH=9.0, with each soaking lasting 15 minutes and followed by low-speed stirring at 150 rpm. Gradient drying was performed under a vacuum of -0.09 MPa: pre-drying at 40℃ for 2 hours, constant-temperature drying at 60℃ for 3 hours, and deep drying at 80℃ for 3 hours to obtain Ni. 0.90 Co 0.04 Mn 0.04 Al 0.02 (OH)2 precursor materials.
[0061] Example 4
[0062] In this embodiment, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni. 0.88 Co 0.05 Mn 0.05 Al 0.02 (OH)₂ is prepared as follows:
[0063] (1) Based on the aluminum doping ratio w=0.02, weigh 21.32g of aluminum sulfate octahydrate, add deionized water to make up to 200mL, and prepare a 0.20 mol / L aluminum sulfate solution (lower limit of concentration); add 0.10g of sodium dodecylbenzenesulfonate as a polarity modifier, and stir at room temperature and 150 rpm for 40min to prepare a monodisperse [Al(OH)4] with a Zeta potential of -25mV. - Homogeneous solution, sealed and allowed to stand for later use.
[0064] (2) Press Ni 0.88 Co 0.05 Mn 0.05Molar proportions were determined by weighing 99.26 g of nickel sulfate hexahydrate, 7.43 g of cobalt sulfate heptahydrate, and 6.46 g of manganese sulfate monohydrate, and adding deionized water to a final volume of 200 mL to prepare a homogeneous sulfate solution with a total metal ion concentration of 1.9 mol / L. 19.00 g of sodium hydroxide was also weighed and added to a final volume of 100 mL of deionized water to prepare a 19% sodium hydroxide solution as a precipitant. The reactor was preheated to 55°C, and nitrogen was introduced to maintain a slightly positive pressure inert atmosphere of 0.03 MPa. A dual-pump synchronous feed system was used, with the sulfate solution feed rate at 23 mL / min. The sodium hydroxide solution was titrated using a PID closed-loop system to precisely control the steady-state pH at 10.8. The reaction was carried out at 400 rpm for 11 hours. After the reaction, impurities were removed by sieving through a 200-mesh sieve to obtain a positively charged NCM framework suspension with a median particle size of 3.5 μm and a surface Zeta potential of +20 mV. This suspension was then kept at a constant temperature and sealed for later use.
[0065] (3) Maintain the temperature inside the reactor at 55℃ and the rotation speed at 300 rpm, [Al(OH)4] - The homogeneous solution was added dropwise to the positively charged NCM framework suspension at a constant rate of 10 mL / min, and the adsorption reaction was carried out at a constant temperature with stirring for 5 h. The pH of the system was finely adjusted to 11.15 using 0.5 mol / L dilute sodium hydroxide solution, and the mixture was aged at 55 °C in a sealed environment for 4 h to obtain the precursor slurry.
[0066] (4) The precursor slurry was centrifuged to separate solids and liquids. The precipitate was washed four times with a weakly alkaline solution at 45℃ and pH=9.0, with each soaking lasting 15 minutes and followed by low-speed stirring at 150 rpm. Gradient drying was performed under a vacuum of -0.09 MPa: pre-drying at 40℃ for 2 hours, constant-temperature drying at 60℃ for 3 hours, and deep drying at 80℃ for 3 hours to obtain Ni. 0.88 Co 0.05 Mn 0.05 Al 0.02 (OH)2 precursor materials.
[0067] Example 5
[0068] In this embodiment, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni. 0.88 Co 0.05 Mn 0.05 Al 0.02 The preparation method of (OH)2 differs from that of Example 4 only in that: in step (3), the pH of the system is finely adjusted to 11.05 using 0.5 mol / L dilute sodium hydroxide solution, and the rest are the same.
[0069] Example 6
[0070] In this embodiment, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni. 0.88 Co 0.05Mn 0.05 Al 0.02 The preparation method of (OH)2 differs from that of Example 4 only in that: in step (3), 0.5 mol / L dilute sodium hydroxide solution is used to fine-tune the pH of the system to 11.10, and the rest are the same.
[0071] Example 7
[0072] In this embodiment, the nickel-cobalt-manganese-aluminum quaternary precursor material is Ni. 0.88 Co 0.05 Mn 0.05 Al 0.02 The preparation method of (OH)2 differs from that of Example 4 only in that: in step (3), 0.5 mol / L dilute sodium hydroxide solution is used to fine-tune the pH of the system to 11.20, and the rest are the same.
[0073] Example 8
[0074] This embodiment prepared a nickel-cobalt-manganese-aluminum cathode material, and the specific preparation method is as follows:
[0075] S1. The nickel-cobalt-manganese-aluminum quaternary precursor material from Example 1 and battery-grade lithium hydroxide were placed in a high-speed powder mixer, with the molar ratio of lithium in the lithium hydroxide to the total metals of the precursor being 1.04:1. The mixture was stirred at 400 rpm for 30 minutes to obtain a mixed powder.
[0076] S2. The mixed powder is transferred to an oxygen atmosphere tube furnace for segmented sintering, with an oxygen concentration ≥95% throughout the process. The segmented sintering is as follows: ① Heating to 450℃ at a heating rate of 4℃ / min and holding for 2.5h; ② Heating to 750℃ at a heating rate of 3℃ / min and holding for 2.5h; ③ Heating to 830℃ at a heating rate of 1.5℃ / min and holding for 12h; ④ Naturally cooling to room temperature with the furnace.
[0077] S3. The sintered product from step S2 is subjected to 300-mesh sieving, iron removal, and powder homogenization treatment to obtain NCMA cathode material LiNi. 0.86 Co 0.06 Mn 0.06 Al 0.02 O.
[0078] Example 9
[0079] This embodiment prepared a nickel-cobalt-manganese-aluminum cathode material. Unlike Example 8, this embodiment used the nickel-cobalt-manganese-aluminum quaternary precursor material prepared in Example 2, and finally obtained LiNi. 0.84 Co 0.06 Mn 0.07 Al 0.03 O.
[0080] Example 10
[0081] This embodiment prepared a nickel-cobalt-manganese-aluminum cathode material. Unlike Example 8, this embodiment used the nickel-cobalt-manganese-aluminum quaternary precursor material prepared in Example 3, and finally obtained LiNi. 0.90 Co 0.04 Mn 0.04 Al 0.02 O.
[0082] Example 11
[0083] This embodiment prepared a nickel-cobalt-manganese-aluminum cathode material. Unlike Example 8, this embodiment used the nickel-cobalt-manganese-aluminum quaternary precursor material prepared in Example 4, and finally obtained LiNi. 0.88 Co 0.05 Mn 0.05 Al 0.02 O.
[0084] Example 12
[0085] This embodiment prepared a nickel-cobalt-manganese-aluminum cathode material. Unlike Example 8, this embodiment used the nickel-cobalt-manganese-aluminum quaternary precursor material prepared in Example 5, and finally obtained LiNi. 0.88 Co 0.05 Mn 0.05 Al 0.02 O.
[0086] Example 13
[0087] This embodiment prepared a nickel-cobalt-manganese-aluminum cathode material. Unlike Example 8, this embodiment used the nickel-cobalt-manganese-aluminum quaternary precursor material prepared in Example 6, and finally obtained LiNi. 0.88 Co 0.05 Mn 0.05 Al 0.02 O.
[0088] Example 14
[0089] This embodiment prepared a nickel-cobalt-manganese-aluminum cathode material. Unlike Example 8, this embodiment used the nickel-cobalt-manganese-aluminum quaternary precursor material prepared in Example 7, and finally obtained LiNi. 0.88 Co 0.05 Mn 0.05 Al 0.02 O.
[0090] Comparative Example 1
[0091] The nickel-cobalt-manganese-aluminum quaternary precursor material in this comparative example is Ni. 0.88 Co 0.05 Mn 0.05 Al 0.02(OH)₂ is prepared as follows:
[0092] (1) Add 0.044 mol nickel acetate, 0.005 mol cobalt acetate, 0.005 mol manganese acetate and 0.002 mol aluminum chloride to 80 mL of ethylene glycol aqueous solution, heat and stir at 40 °C and 400 r / min for 6 h to obtain a mixed metal solution;
[0093] (2) Add 1.8018 g (0.03 mol) of urea and 1.5812 g (0.02 mol) of ammonium bicarbonate to the mixed metal solution obtained in step (1). Heat and stir at 40°C and 400 r / min for 2 h. Then place it in a sealed stainless steel reactor with a polytetrafluoroethylene liner and carry out a solvothermal reaction at 180°C for 12 h. Filter the solution in a Bush funnel using a vacuum filter. Wash the filter with deionized water and ethanol six times in succession. Dry the solution in a forced-air drying process at 80°C for 20 h to obtain the nickel-cobalt-manganese-aluminum quaternary precursor Ni. 0.88 Co 0.05 Mn 0.05 Al 0.02 (OH)2.
[0094] Comparative Example 2
[0095] This comparative example prepared a nickel-cobalt-manganese-aluminum cathode material, using the same preparation method as in Example 8. The only difference was that this comparative example used the nickel-cobalt-manganese-aluminum quaternary precursor material prepared in Comparative Example 1, ultimately yielding LiNi. 0.88 Co 0.05 Mn 0.05 Al 0.02 O.
[0096] Performance testing:
[0097] (1) Microstructure and sphericity test: The nickel-cobalt-manganese-aluminum quaternary precursors prepared in Examples 1-7 and Comparative Example 1 were used as samples. A SU8010 field emission scanning electron microscope (SEM) was used with a test voltage of 5 kV and a magnification of 5000-20000 times to observe the sphericity of the particles, surface porosity, grain packing state and framework defects. The test results are shown in Table 1.
[0098] Test results show that the sphericity of the samples in the embodiments of the present invention is concentrated in the range of 0.93 to 0.96, with Examples 5 and 6 being the best, reaching 0.96, all meeting the industry standard of ≥0.92 for high-quality precursors; the sphericity of Comparative Example 1 is only 0.78, far below the industry standard.
[0099] (2) Element distribution uniformity test: The nickel-cobalt-manganese-aluminum quaternary precursor materials prepared in Examples 1-7 and Comparative Example 1 were used as samples. The element distribution of the single particle profile was scanned by an EDS surface scan and line scan energy dispersive spectrometer with SEM. The radial distribution of Ni, Co, Mn and Al elements was tested, and the degree of aluminum segregation was evaluated.
[0100] EDS characterization showed that in all embodiments of the present invention, the quaternary elements Ni, Co, Mn and Al were uniformly distributed radially, with no aluminum-rich surface and aluminum-poor core segregation. The high-aluminum doped embodiment 2 still maintained atomic-level uniform solid solution. In contrast, Comparative embodiment 1 showed severe aluminum segregation, with the aluminum content on the surface being much higher than that in the core, and the element distribution dispersion was extremely high.
[0101] (3) Tap density test: The nickel-cobalt-manganese-aluminum quaternary precursor materials prepared in Examples 1-7 and Comparative Example 1 were used as samples. The FT-100B powder tap density meter was used, and the number of vibrations was 3000. After weighing the powder to a constant mass, the tap density value was read. The test results are shown in Table 1.
[0102] Test results show that the tap density of the embodiments of the present invention reaches 2.12-2.25 g / cm³, which is close to the industry standard for high-compaction precursors, with minimal batch-to-batch variation and excellent packing performance. Comparative Example 1 has a tap density of only 1.65 g / cm³, a reduction of 26.7% compared to the optimal sample of the present invention. The high sphericity and dense, defect-free particle structure are the core reasons for the high tap density. The preparation method of the present invention can effectively improve the packing density of powder, directly increasing the tap density of battery electrodes and the energy density of individual cells.
[0103] (4) Pore structure test: The nickel-cobalt-manganese-aluminum quaternary precursor materials prepared in Examples 1-7 and Comparative Example 1 were used as samples. The specific surface area, average pore size, and pore distribution were tested using a liquid nitrogen adsorption BET surface area and pore size analyzer to evaluate the rationality and compactness of the internal pores of the particles. The test results are shown in Table 1.
[0104] Test results show that the specific surface area of the embodiment of the present invention is 16.8-19.8 m² / g and the average pore size is 10.2-13.8 nm. The pore size is a single peak with a narrow distribution and the pores are regular and controllable. The specific surface area of the comparative example 1 is as high as 32.4 m² / g and the average pore size is 25.8 nm. The pore size is multi-peaked and scattered, and the defect pores are dense.
[0105] (5) Electrochemical cycling performance test: Using the nickel-cobalt-manganese-aluminum cathode materials prepared in Examples 8-14 and Comparative Example 2 as samples, the cathodes were prepared according to conventional methods, and CR2032 coin cells were assembled. The voltage range was 2.8-4.3 V, the temperature was 25℃, and the constant current charge-discharge test was conducted at 1C for 500 cycles. The capacity retention rate was recorded. The test results are shown in Table 2.
[0106] Test results show that the capacity retention rate of the samples of this invention after 500 cycles at 1C is 85.4% to 92.6%, with the high-aluminum doped Example 9 and the optimal pH gradient Examples 12-13 having a retention rate exceeding 91%; while the comparative example 2 only has a retention rate of 62.3%. This indicates that the nickel-cobalt-manganese-aluminum cathode material of this invention suppresses charge-discharge phase transition distortion and microcrack propagation, significantly improving structural stability.
[0107] (6) Rate performance test: The nickel-cobalt-manganese-aluminum quaternary cathode materials prepared in Examples 8-14 and Comparative Example 2 were used as samples. They were discharged at 0.2C, 0.5C, 1C, 2C and 3C rates at 25℃, respectively. The discharge capacity at different rates was compared and the polarization and kinetic performance was evaluated. The test results are shown in Table 2.
[0108] Test results show that the sample of this invention exhibits a smooth capacity decay across the full rate range of 0.2C to 3C, and can still maintain a high capacity of 176.8 to 186.5 mAh / g at the high rate of 3C, demonstrating excellent rate retention. In contrast, the comparative example 2 shows severe polarization at high rates, with a 3C discharge capacity of only 128.6 mAh / g, indicating a significant deterioration in high-rate performance.
[0109] The cathode material of this invention exhibits stable capacity across the entire rate range of 0.2C to 3C, with low polarization, a stable voltage plateau, and excellent capacity retention at high rates. This is attributed to the material's uniform elemental composition, intact lattice, and reasonable porosity, resulting in unobstructed lithium-ion diffusion channels and low charge transfer impedance. Furthermore, uniform aluminum doping optimizes the lattice interlayer spacing, further enhancing ion migration rates. In contrast, the cathode material of Comparative Example 2 suffers from numerous structural defects and aluminum segregation leading to localized impedance unevenness, resulting in severe polarization and a precipitous drop in capacity at high rates, exhibiting extremely poor kinetic performance.
[0110] (7) Thermal safety performance test: The nickel-cobalt-manganese-aluminum quaternary cathode materials prepared in Examples 8-14 and Comparative Example 2 were used as samples. A differential scanning calorimeter (DSC) was used to test the thermal decomposition temperature and exothermic peak intensity of the cathode materials in the fully lithium-intercalated state at a heating rate of 5℃ / min to evaluate the thermal stability and safety performance. The test results are shown in Table 2.
[0111] Test results show that the thermal decomposition temperatures of the samples in the embodiments of the present invention reach 221.6–242.3℃, and the exothermic peak area is 452–648 J / g, with Example 9 exhibiting the best thermal stability. Comparative Example 2, however, has a thermal decomposition temperature of only 205.2℃ and an exothermic peak area as high as 892 J / g, exhibiting intense exothermic activity and poor thermal stability. This indicates that the uniformly dissolved aluminum atoms in the nickel-cobalt-manganese-aluminum quaternary precursor material of the present invention can effectively stabilize the layered lattice, suppress high-temperature lattice collapse and electrolyte side reactions, and reduce the risk of thermal runaway.
[0112] Table 1. Test Results of Physical Structure and Performance of Precursor Samples
[0113]
[0114] Table 2. Test Results of Electrochemical and Thermal Safety Performance of Cathode Material Samples
[0115]
[0116] Note: The sphericity values in Table 1 range from 0 to 1, with values closer to 1 indicating higher sphericity; in Table 2, higher thermal decomposition temperatures and smaller exothermic peak areas indicate better thermal stability and higher safety.
[0117] The foregoing description includes examples from this specification. Of course, for the purposes of describing this specification, it is impossible to describe every conceivable combination of components or methods; however, those skilled in the art will understand that many other combinations and arrangements are possible. Therefore, this specification is intended to cover all such changes, modifications, and variations that fall within the spirit and scope of the appended claims. Furthermore, with regard to the use of the term "comprising" in the detailed description or claims, the term is intended to be inclusive in a manner similar to the term "including," as interpreted when "comprising" is used as a transitional word in the claims.
[0118] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a nickel-cobalt-manganese-aluminum quaternary precursor material, characterized in that, The nickel-cobalt-manganese-aluminum quaternary precursor material is Ni x Co y Mn z Al w (OH)₂, satisfying x + y + z + w = 1, and 0.80 ≤ x ≤ 0.90, 0.04 ≤ y ≤ 0.08, 0.04 ≤ z ≤ 0.08, 0.01 ≤ w ≤ 0.03; the preparation method includes the following steps: Weigh aluminum sulfate octadechydrate and add it to deionized water to prepare an aluminum sulfate solution. Add an anionic polar modifier to the aluminum sulfate solution and stir at 120–180 rpm for 30–50 min to obtain [Al(OH)4]. - Homogeneous solution; Weigh nickel sulfate hexahydrate, cobalt sulfate heptahydrate, and manganese sulfate monohydrate according to the target product molar ratio, dissolve them in deionized water, and prepare a homogeneous sulfate solution. Preheat the reactor to 50-60°C and maintain the temperature. Purge with nitrogen to maintain a pressure of 0.02-0.04 MPa. Use two pumps to pump the homogeneous sulfate solution and sodium hydroxide solution into the reactor respectively. Control the pH in the reactor to 10.5-11.
0. Stir the reaction at 350-450 rpm for 9-13 hours to obtain a positively charged NCM framework suspension. [Al(OH)4] was stirred at 50–60°C and 260–340 rpm. - The homogeneous solution was added dropwise at a constant rate to the positively charged NCM framework suspension. After the addition was completed, the mixture was stirred continuously at a constant temperature for 3 to 7 hours. Then, the pH was adjusted to 11.00 to 11.20, and the mixture was aged in a sealed container at 50 to 60°C for 3 to 5 hours to obtain the precursor slurry. The precursor slurry was centrifuged to separate the precipitate, which was then washed with a weakly alkaline solution with a pH of 8.5–9.
5. The washed precipitate was then subjected to vacuum gradient drying to obtain the nickel-cobalt-manganese-aluminum quaternary precursor material.
2. The preparation method according to claim 1, characterized in that, The concentration of the aluminum sulfate solution is 0.17–0.23 mol / L, and 0.05–0.15 g of anionic polarity modifier is added to each liter of the aluminum sulfate solution.
3. The preparation method according to claim 1, characterized in that, The anionic polarity modifier is selected from at least one of sodium dodecylbenzenesulfonate, sodium dodecyl sulfonate, sodium tetradecyl sulfonate, sodium tartrate, sodium citrate, sodium gluconate, and sodium lignin sulfonate.
4. The preparation method according to claim 1, characterized in that, The total metal ion concentration in the homogeneous sulfate solution is 1.7–2.1 mol / L; and / or, The concentration of the sodium hydroxide solution is 17–21 wt%.
5. The preparation method according to claim 1, characterized in that, The homogeneous sulfate solution is pumped into the reaction vessel at a rate of 18–28 mL / min; and / or, The sodium hydroxide solution was titrated using a PID closed-loop follower titration method.
6. The preparation method according to claim 1, characterized in that, The [Al(OH)4] - The homogeneous solution was added dropwise to the positively charged NCM framework suspension at a constant rate of 7–13 mL / min.
7. The preparation method according to claim 1, characterized in that, The vacuum degree of the vacuum gradient drying is -0.11 to 0.07 MPa, and the vacuum gradient drying procedure is as follows: first, dry at 35 to 45°C for 1 to 3 hours, then dry at 55 to 65°C for 2 to 4 hours, and finally dry at 75 to 85°C for 2 to 4 hours.
8. A nickel-cobalt-manganese-aluminum quaternary precursor material, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
9. An electrode, characterized in that, The electrode comprises the nickel-cobalt-manganese-aluminum quaternary precursor material as described in claim 8.
10. A battery, characterized in that, The battery includes the electrodes as described in claim 9.